A Concrete Naming Convention for Small Intervals - Laurence S Willis (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2025)
In tuning theory, names proliferate for the bewildering array of intervals available to theorists and scholars. Of particular difficulty is the naming of small intervals: as a group these are generally referred to as commas, following the Greek practice. The various names used for small intervals derive from many different sources, some etymologically related to the ancient practice and some to the origin of the interval in more recent music theory. The problem with this situation is that while they remain fascinating from a scholarly perspective, these names are unwieldy for technical usage, sometimes barely understandable for an informed audience, and generate in-group speech that must be overcome before tuning texts can be understood. This article devises a concrete and reproducible naming convention for small musical interval, starting with a small set of ancient Greek names and attaching these to specific pitch bands.
Keywords: Tuning; Commas; Boethius